2021
DOI: 10.3390/nano11092445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Characterization of Epoxy Composites Containing Highly Entangled As-Received and Acid Treated Carbon Nanotubes

Abstract: Huntsman–Merrimack MIRALON® carbon nanotubes (CNTs) are a novel, highly entangled, commercially available, and scalable format of nanotubes. As-received and acid-treated CNTs were added to aerospace grade epoxy (CYCOM® 977-3), and the composites were characterized. The epoxy resin is expected to infiltrate the network of the CNTs and could improve mechanical properties. Epoxy composites were tested for flexural and viscoelastic properties and the as-received and acid treated CNTs were characterized using Field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Sometimes, it is used to describe a percolated network of nanotubes . When used in this way, it is often in contrast to dispersed nanotubes and is not always intended to imply a special load transfer phenomenon. In nanotube networks, the word entanglement is sometimes used to describe the effects that are induced by nanotubes that simultaneously belong to different bundles and thus serve at interconnects between bundles. For example, a sample that is observed under microscopy to contain little alignment and many pores may be colloquially described as more entangled than another sample that is highly aligned with few pores and thus presumably few bridged bundles.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, it is used to describe a percolated network of nanotubes . When used in this way, it is often in contrast to dispersed nanotubes and is not always intended to imply a special load transfer phenomenon. In nanotube networks, the word entanglement is sometimes used to describe the effects that are induced by nanotubes that simultaneously belong to different bundles and thus serve at interconnects between bundles. For example, a sample that is observed under microscopy to contain little alignment and many pores may be colloquially described as more entangled than another sample that is highly aligned with few pores and thus presumably few bridged bundles.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the low density, a significant aspect ratio and a large surface area make them potential structures to reinforce composite materials. [ 14–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the low density, a significant aspect ratio and a large surface area make them potential structures to reinforce composite materials. [14][15][16][17] The dispersion of nano reinforcements in the matrix, in order to obtain cluster-free mixtures, and a good strength between the nanofiller and epoxy interfaces are the main factors that affect the performance of nanocomposite adhesives. [1,4,18] Other aspects that influence adhesive performance are the thickness of the adherent, the roughness of the surface adherent, the thickness of the bond line and the wettability of the adhesive over the surface where it is applied.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of strategies have been pursued to develop structural CNT composites. Some studies showed the results by introducing aligned CNTs into conventional fiber-reinforced composites to achieve greater strength [7][8][9][10][11][12][13] . Of course, such approaches lead only to incremental improvements in properties over current CF composites.…”
Section: Introductionmentioning
confidence: 99%